A combined XFEM and cohesive zone model for composite laminate microcracking and permeability. (February 2015) - Grogan, D.M.; Ó Brádaigh, C.M.; Leen, S.B.
Abstract: A novel computational methodology for predicting three-dimensional microcracking and permeability in composite laminates is presented. The methodology simulates microcrack initiation and propagation using the extended finite element method (XFEM) and delamination using a mixed-mode cohesive zone model. Random microcrack initiation is modelled using a random (Weibull) distribution of fracture strengths. The Weibull distribution is adjusted to account for specimen volume, allowing mesh independent crack density predictions. An alternate method is also investigated, based on an elemental representation of defects using measured void geometry. The predicted microcracking and damage distributions are shown to correlate closely with 3D X-ray CT (computed tomography) scans of cryogenically cycled specimens. Crack opening displacements are consistent with laminate test measurements. Permeabilities, based on the dimensions of the leak paths, were found to be within the measured range for various CF (carbon fibre)/PEEK materials.